2010
DOI: 10.1007/s11596-010-0547-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of human epicardial adipose tissue in coronary artery atherosclerosis

Abstract: This study examined the adipocytokine-vascular interactions and link between epicardial adipose tissue and coronary artery atherosclerosis. Thirty-four patients undergoing open heart surgery were chosen randomly, and divided into group I (non-coronary artery disease group) and group II (coronary artery disease group). Blood samples were taken through peripheral vein prior to surgery. Plasma levels of a panel of proteins (adiponectin, IL-10, TNF-α) were detected by using ELISA. Epicardial adipose tissue was tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The single probe that interrogated this gene in our study was also differentially up-regulated in EAT compared to SAT (fold change = 1.20), but was not significant. Another study suggested that the expression of adiponectin (ADIPOQ) was lowered in EAT compared to SAT [25]. Again our results were in the same direction (fold change = 0.84 comparing EAT vs SAT), but not significant.…”
Section: Discussionsupporting
confidence: 65%
“…The single probe that interrogated this gene in our study was also differentially up-regulated in EAT compared to SAT (fold change = 1.20), but was not significant. Another study suggested that the expression of adiponectin (ADIPOQ) was lowered in EAT compared to SAT [25]. Again our results were in the same direction (fold change = 0.84 comparing EAT vs SAT), but not significant.…”
Section: Discussionsupporting
confidence: 65%
“…For example, EAT in patients with coronary artery disease (CAD) exhibit a greater proinflammatory profile than in non-CAD counterparts (37). Both mRNA expression and protein levels of proinflammatory cytokines such as tumor necrosis factors-a (TNF-a), interleukin (IL)-6, and monocyte chemoattractant protein (MCP-1) have been shown to be upregulated, and anti-inflammatory adiponectin to be downregulated, after adjustment for concurrent hypertension, diabetes, dyslipidemia, and body mass index (BMI) (38)(39)(40)(41)(42). Consistent with the rise in MCP-1, histological analysis of EAT from CAD patients exhibited infiltration by M1 macrophages and CD68 þ cells (43).…”
Section: Eat As a Pathophysiological Inflammatory Substratementioning
confidence: 99%
“…4,5 Furthermore, the EF shows a greater expression and secretion of adipokines and inflammatory chemokines [tumor necrosis factor (TNF)-alpha, interleukin (IL)-8, MCP-1, C-reactive protein (CRP), IL-1β, and IL-6] and infiltration of the chronic inflammatory cell as macrophage in pathological conditions. 6 For these features, EF plays an important role in modifying the vascular endothelial function and promoting the growth of coronary atherosclerosis. 7…”
Section: Introductionmentioning
confidence: 99%